Implementasi Teori Konstruksi Sosial dalam Penelitian Public Relations - Ani Yuningsih (MediaTor (Jurnal Komunikasi), 2006)
How far has PR research been conducting in order to simultaneously update the rapid development in the field? The answer for this question will indicate whether or onot PR performance has succeeded in fulfilling its functions among public. Adopting Berger and Luckmann perspective over the construction of social reality, a PR corporate will achieve a new level of existence by the process of habitualization involving an effective pattern of communication. PR role is no more than bridging, managing, and maintaining traditions based on members of community’s experiences, and then transforming through the organization.